OPTIMALISASI WAKTU DAN BIAYA PEMBANGUNAN GEDUNG ASRAMA HAJI EMBARKASI TRANSIT WAIHERU AMBON DENGAN MENGGUNAKAN METODE TIME COST TRADE OFF - Dimas Fahrul; Octovianus Jamlaay; Maslan Abdin (Jurusan Teknik Sipil, 2023)
The construction of the Waiheru Ambon Hajj Embarkment Transit Building was intended to be the object of this study because it was based on the background that occurred in the project, namely delays. Based on secondary data obtained from the project, the Budget Plan (RAB) and Time Schedule are used as project’s duration and normal costs of the project. Then the time cost trade off method is applied which aims to be able to reduce the duration and find out the total cost needed so that the project can reach the planned time target so as not to experience delays. Dimyati, H (2014) explained that there are two reasons why acceleration of construction of construction projects is carried out. First, because off the desire of the owner so that the project can be completed before the deadline for project completion. Second, because in the implementation of the project there is a delay in time or progress, the acceleration must be carried out.This is where the importance of a plan that must be prepared carefully so that cosis that will have an impact on acceleration the project can be controlled properly. Time acceleration in this project, using the Time Cost Trade Off Method with the principle of increasing overtime working hours. After accelerating with the addition of 3 hours, it could save time by 0.11% where the project cost is reduced by around 0.003%. Meanwhile, the addition of 2 hours could save time by 0.10% where the project cost is also reduced by around 0.003%. While the optimal duration and optimal costs were known in the alternative addition of 3 hours of overtime obtained 94 working days at a cost of IDR 27,388,709,338.20. Meanwhile, in addition to 2 hours of overtime, 95 working days were obtained at a cost of IDR 27,388,026,130.23.